Indicator species and co-occurrence in communities of arbuscular mycorrhizal fungi at the European scale. (December 2016) - Bouffaud, Marie-Lara; Creamer, Rachel E.; Stone, Dote; Plassart, Pierre; van Tuinen, Diederik; Lemanceau, Philippe; Wipf, Daniel; Redecker, Dirk
Abstract: Utilizing a European transect of 54 soil samples, comprising of grasslands, arable and forest sites, we analyzed community composition of Arbuscular Mycorrhizal Fungi (AMF, Glomeromycota) using pyrosequencing of the Internal Transcribed Spacer region. We found a significant influence of environmental factors (soil pH and organic carbon or land use) on the community composition, but these factors did not fully explain the overall amount of AMF diversity. Geographical distance of sites also significantly affected community structure, indicating significant dispersal limitations of Glomeromycota at the European scale. Indicator species have been proposed by land use and physicochemical soil parameters. Generalist species were also identified, that were found occurring in a large proportion of the sample sites. By co-occurrence analysis of species pairs we show that, at this spatial scale, closely-related species are more likely to co-occur than distantly-related ones. This suggests that environmental filtering is a more dominant driving force in community assembly than fungal competition. Highlights: Significant geographic structure across AMF communities at the European scale. Indicator species for land use and physicochemical soil parameters. Closely-related species are more likely to co-occur than distantly-related ones.